KEPEMILIKAN INSTITUSIONAL, PROFITABILITAS, DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK UKURAN PERUSAHAAN SEBAGAI PEMODERASI - Evi Maria; Laura Agnes Cahyani (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2025)
This research aims to analyze the effect of institutional ownership, profitability, and leverage on tax avoidance with firm size as moderating. The population of this research were LQ45 companies listed on the Indonesia Stock Exchange in 2020-2022. By using purposive sampling, the samples used in this research were 75 observational data from 25 companies. The data in this research were analyzed using Partial Least Square (PLS). The results showed that institutional ownership, profitability, and leverage has effect on tax avoidance. In addition, firm size is able to moderate the effect of profitability and leverage on tax avoidance, but firm size is not able to moderate the effect of institutional ownership on tax avoidance